Intimate partner violence and exclusive breastfeeding of infants: analysis of the 2013 Nigeria demographic and health survey - Tolulope Ariyo; Quanbao Jiang (BMC, 2021)
Abstract Background Existing knowledge on the relationship between intimate partner violence (IPV) and exclusive breastfeeding (EBF) in the context of Nigeria is minimal and limited to a lifelong measure of IPV experience. An abuse experienced a long time ago may not have as much negative effect as that encountered at a more proximal time to the breastfeeding phase. To this effect, we examined this relationship with maternal IPV experienced around the time of pregnancy and postpartum. Method We analyzed data from the 2013 Nigeria Demographic and Health Survey. The sample includes 2668 breastfeeding mothers having a child aged under 6 months. The outcome variable was EBF or mixed-feeding (24 h recall). The exposure variables were: the maternal experience of psychological, physical, and sexual intimate partner violence. Also, there was an experience of any form of IPV and frequency score of intimate partner violence. Analysis includes chi-square and t-test bivariates, complete case and imputed logistic regressions for binary outcome. Results In the imputed analysis, compared to mothers who experienced no IPV, those who experienced IPV had a 26% reduced likelihood of EBF practice (AOR 0.74; 95% CI 0.55, 1.00). Also, a unit dose of maternal IPV experience was associated with a 5% reduced likelihood of EBF practice (AOR 0.69; 95% CI 0.49, 0.98). Among the three forms of IPV, physical IPV had the highest effect size. Physical IPV was associated with a 37% reduced likelihood of EBF practice (AOR 0.63; 95% CI 0.44, 0.90), while psychological IPV was associated with a 34% reduced likelihood of EBF practice (AOR 0.66; 95% CI 0.47, 0.92), when compared to the respective reference groups. On the other hand, those who reported sexual IPV were just as likely to breastfeed as those who did not (AOR 0.94; 95% CI 0.62, 1.41). Conclusions In this study, maternal IPV is associated with EBF practice. Policies aimed at promoting EBF should also be framed to combat IPV against pregnant women and nursing mothers.